Study of metacognitive awareness at the individual level of students across study programs using Rasch modeling - Moh. Irma Sukarelawan; Panji Hidayat; Widodo Widodo (Universitas Ahmad Dahlan, 2024)
Evaluating students' metacognitive awareness is necessary to identify weaknesses and strengths in managing their cognition, which can help develop effective cognitive regulation to overcome academic challenges. Therefore, this research aims to examine students' level of metacognitive awareness using Rasch modeling. Survey research was conducted on 122 students at FKIP. Metacognitive awareness was evaluated using the 18-item Jr. MAI, and each item uses a 5-point Likert rating scale. Jr. MAI in the Google form is distributed for 2-3 weeks. Metacognitive awareness data was analyzed using the Logit Value of Person (LVP) approach and the Person Wright Map in Rasch modeling. The analysis results show that the distribution of metacognitive awareness shows that the majority of physics education students tend to have a higher level of metacognitive awareness, while the distribution of metacognitive awareness among elementary school teacher education students is more even across all categories. The implication of this research is the need to develop effective cognitive regulation in overcoming academic challenges through evaluating students' metacognitive awareness.